When Measure Matters Coresidency, Truncation Bias, and Intergenerational Mobility in Developing Countries - Emran, M. Shahe (World Bank E-Library Archive, 2016)
Biases from truncation caused by coresidency restriction have been a challenge for research on intergenerational mobility. Estimates of intergenerational schooling persistence from two data sets show that the intergenerational regression coefficient, the most widely used measure, is severely biased downward in coresident samples. But the bias in intergenerational correlation is much smaller, and is less sensitive to the coresidency rate. The paper provides explanations for these results. Comparison of intergenerational mobility based on the intergenerational regression coefficient across countries, gender, and over time can be misleading. Much progress on intergenerational mobility in developing countries can be made with the available data by focusing on intergenerational correlation